The Triple Spar Campaign: Implementation and Test of a Blade Pitch Controller on a Scaled Floating Wind Turbine Model. (October 2017) - Yu, W.; Lemmer, F.; Bredmose, H.; Borg, M.; Pegalajar-Jurado, A.; Mikkelsen, R.F.; Larsen, T. Stoklund; Fjelstrup, T.; Lomholt, A.K.; Boehm, L.; Schlipf, D.; Armendariz, J. Azcona; et al.
Abstract: In this project by the University of Stuttgart, DTU Wind Energy and CENER, a real-time blade-pitch control system was implemented on a scaled model in a combined wind-and-wave tank. A simplified low-order simulation model including aerodynamics, hydrodynamics, mooring dynamics and structural dynamics was used to design the controller. Some effort has been made to investigate the influence of different gain scheduling methodologies of the collective blade-pitch controller on the dynamic behavior of the floating wind turbine. The issue relating to the negative aerodynamic damping is also investigated in order to find out whether the effects seen in simulation models can be equally reproduced by model tests. Additionally, wind and wave-induced responses with different gain scheduling methodologies and the difference to the tests without blade-pitch control are discussed. A solution for the hardware implementation of the real-time controller has been introduced. The developed controller is proven to function throughout the test campaign, which also proves the reliability of the simplified simulation model for controller design. It has been shown that with the low-Reynolds rotor it is possible to control the rotor speed at Froude-scaled frequencies by actuating the blade pitch angle.